Dynamic Antifouling of Catalytic Pores Armed with Oxygenic Polyoxometalates. Issue 7 (31st March 2015) - Squarcina, Andrea; Fortunati, Ilaria; Saoncella, Omar; Galiano, Francesco; Ferrante, Camilla; Figoli, Alberto; Carraro, Mauro; Bonchio, Marcella
<x xml:space="preserve">Abstract</x> A novel stimuli‐responsive strategy against the irreversible fouling of porous materials and surfaces is presented herein. This is based on the molecular design of catalytic pore walls that foster a chemo‐mechanical, self‐cleaning behavior under neutral pH and mild conditions of pressure and temperature. This approach builds on bioinspired remediation mechanisms involving natural catalase enzymes for H2O2 dismutation and endogenous oxygen production. It is thus demonstrated that a very efficient antifouling activity is observed when the material pores are armed with oxygen evolving catalysts that are known to liberate nascent oxygen gas when exposed to H2O2 as chemical trigger. To this aim, the catalase‐like behavior of the tetra‐ruthenium substituted polyoxometalate (Ru4(SiW10)2), has been exploited for in‐pore oxygen evolution so to induce an active fluid mixing and the displacement of foulant particles. The present study includes the fabrication of hybrid polymeric films with porous architecture embedding Ru4(SiW10)2 as artificial catalase to guarantee the material self‐defense against pore occlusion and oxidative damage with aqueous H2O2 as mild chemical effector. The self‐catalytic "in‐pore" remediation is readily applied to various materials/interfaces with porous texture and high surface area with the aim to provide long‐lasting functional performances.